Chemical and Physical Pathways for Fabricating Flexible Superamphiphobic Surfaces with High Transparency - Sahoo, Bichitra; Yoon, Kukro; Seo, Jungmok; Lee, Taeyoon (MDPI, 2018)
Since the discovery of the self-cleaning properties of the lotus effect, the wetting of surfaces were intensively investigated due to their potential application in many industrial sectors. The transparency of flexible liquid repellent coatings are a major industrial problem and their economic consequences are widely known. Hence, a comprehensive understanding of the developments of flexible and transparent superamphiphobic surfaces is required in a number of technological and industrial situations. In this review, we aim to discuss the progress in the design, synthesis, fabrication techniques, and applications of flexible and transparent superamphiphobic surfaces. We start with an introduction, exploring the contact angles and wetting states for superhydrophilic, superhydrophobic, and superoleophobic surfaces, and continue with a review of the wetting transition of such surfaces. Then, we highlight the fabrication techniques involved for the preparation of flexible and transparent superamphiphobic surfaces. This review also discusses the key issues in the fabrication process and surfaces, and their features in improving durability characteristics and self-repellent performance. Then we suggest various recommendations for the improvement of mechanical durability along with potential future directions towards more systematic methods that will also be acceptable for industry. Finally, we conclude with some challenges and potential applications.
Keywords: SELF-CLEANING SURFACES; SUPERHYDROPHOBIC SURFACES; SUPEROMNIPHOBIC SURFACES; BROAD-BAND; SUPEROLEOPHOBIC SURFACES; HIERARCHICAL STRUCTURES; MECHANICAL DURABILITY; ENVIRONMENTALLY-SAFE; RECENT PROGRESS; FILMS